Neo-protectionism and economic growth - Franz Peter Lang (Intereconomics, 1984)
The world economy is threatening to find itself in a vicious circle of escalating protectionism. Franz Peter Lang explains the dangers and consequences of this. Gary Banks argues that the “new protectionism” is not so much a temporary by-product of the recession as the external manifestation of internal domestic struggles between vested interests and the public interest, and pleads for the establishment of a “transparency institution”.
Keywords: 330; Protectionism